Pour un usage externe des théories de la science-fiction - Simon Bréan (ReS Futurae)
Science fiction puts into play a whole range of dynamic processes, organized around a central principle, the construction of a world openly distinct from ours, but that the text gives us to enjoy and feel as plausible. These processes all respond to the same objective: a relationship between the world of fiction and the real world that presupposes a form of rational continuity, as well as referential ruptures and conceptual innovations, which we have proposed to call “speculative ontological regime”. From the examination of Hervé Le Tellier’s L’Anomalie (2020), Jean Echenoz’s Vie de Gérard Fulmard (2020) and Jean- Philippe Jaworski’s Janua Vera (2007), we are going to question what, in the analysis of processes associated with science fiction, is transposable or stimulating to approach all fictions belonging to any materialist ontological regime (realism and fantasy). Thus, in addition to the examination of case studies testing the limits between science fiction and realism, it is possible to start from the notion of novum (D. Suvin) to wonder what it means to consider the other ontological regimes as spaces of “non-novum”: not necessarily the cognitive inertia that Suvin lends them, but rather specific strategies to be put in comparison with the novum and its cognitive estrangement.